Active relaxation counteracts the effects of ego depletion on performance under evaluative pressure in a state of ego depletion - Englert, C.; Bertrams, A. (Sportwissenschaft, 2016)
We tested the assumption that active relaxation following an ego-depletion task counteracts the negative effects of ego depletion on subsequent performance under evaluative pressure. N=39 experienced basketball players were randomly assigned to a relaxation condition or to a control condition, and then performed a series of free-throws at two points of measurement (T1: baseline vs. T2: after working on a depleting task and either receiving active relaxation or a simple break). The results demonstrated that performance remained constant in the relaxation condition, whereas it significantly decreased in the control condition. The findings are in line with the notion that active relaxation leads to a quicker recovery from ego depletion. Es wurde die Annahme untersucht, dass Personen durch die Ausübung aktiver Entspannungstechniken nach einer Selbstkontrollaufgabe die negativen Effekte von Ego Depletion auf die anschließende Leistung unter Druck kompensieren können. N = 39 erfahrene Basketballspieler wurden zufällig einer Entspannungsbedingung oder einer Kontrollbedingung zugeordnet und führten eine Serie von Freiwürfen zu zwei Messzeitpunkten durch (T1: Baseline vs. T2: nach einer Ego Depletion Aufgabe und entweder einer Entspannungsübung oder einer einfachen Pause). In der Entspannungsbedingung blieb die Leistung zu beiden Messzeitpunkten konstant, jedoch schnitten die Probanden der Kontrollbedingung zu T2 signifikant schlechter ab als zu T1. Die Ergebnisse deuten darauf hin, dass aktive Entspannungsübungen zu einer schnelleren Regeneration erschöpfter Selbstkontrollkraft beitragen können.